Gender Balance in Norwegian Academia: Present State and Future Scenarios - Lekve, Kyrre; Gunnes, Hebe (Frontiers in Education, 2022)
Gender balance (both sexes being represented by at least 40 percent) in academia has long been a goal. In this study, we present a model for the inert changes in the proportion of female full professors and associate professors at four research universities in Norway and stipulate future scenarios. Data from 1977 to 2019 were fitted to a sigmoid model. The results indicate that for all full professors, gender balance will be reached sometimes in the mid 2030’s. Gender balance among all associate professors is already achieved. However, when the data is split into fields of research and development (fields of R&D), pronounced differences were seen. The results indicate that we will not achieve gender balance among full professors within humanities and the arts, while the proportion of female professors within Natural sciences and Engineering and technology cannot be properly modelled. Contrary, gender balance among associate professors will be achieved within all fields of R&D apart from engineering and technology, while natural sciences cannot be modelled properly. Essentially this model exercise illustrates what will happen with the gender balance in academia if no interventions are made. If so, we might not achieve gender balance in all fields of science.